Analisis Good Corporate Governance dalam Transformasi Digitalisasi Perbankan (Studi Pada Aplikasi Pelayanan “Pemda Online” Bank Pembangunan Daerah Lampung) - Rendito Rendito; Dedy Hermawan; Intan Fitri Meutia (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2020)
Good Corporate Governanceis a set of rules that organize the relationship between a company and its stakeholders that are, the shareholders, commissioner councils, the government, the community and employees in fulfilling the rights and obligations of the company in protecting the interests of stakeholders based on sound corporate values. This study aims to obtain an overview and analysis of the implementation of GCG, indications of GCG in supporting the transformation of banking digitalization in improving the quality of service innovation through the application of online local government services as an application that supports transparency and accountability in regional financial management and regarding the obstacles in implementing GCG in supporting digitalization transformation through online local government at the Lampung Regional Development Bank. This type of research is a descriptive study with a qualitative approach. The results of this study indicate that the implementation of GCG at the Lampung Regional Development Bank has been carried out in accordance with the principles of GCG based on: transparency, accountability, responsibility, independence and equality, but the implementation has not been carried out properly, due to several prevent factors among which is: not yet fulfilled the core management of the Lampung Regional Development Bank and the limited network of IT